Використання методики таксономічного аналізу для оцінювання рівня продовольчої безпеки України - Михайлик, Ольга Михайлівна; Страшинська, Лариса Володимирівна (My University, 2023)
У статті доведено практичну цінність застосування спеціальних економіко-математичних методів для проведення процесу оцінювання рівня продовольчої безпеки держави. Запропоновано для спрощеної формалізації розрахунків індексу продовольчої безпеки використати метод таксономії. Запропонований підхід дозволяє оцінити ступінь сукупного впливу факторних ознак на рівень забезпечення продовольчої безпеки держави. Визначено систему індикаторів (множинних ознак) для оцінки інтегрального показника рівня продовольчої безпеки за ретроспективний період з 2015 по 2021 рік, які створюють ваговий (стимулюючий, дестимулюючий) внесок в загальний індекс продовольчої безпеки. Згідно правила проведення таксономічної процедури нормовано індикатори вхідної матриці, визначено координати точки-еталону, визначено «відхилення» між окремими індикаторами та базовою порівняння, розраховано інтегральний (таксономічний) показник рівня продовольчої безпеки України. The article proves the practical value of using special economic and mathematical methods for the process of assessing the level of state food security. It is proposed to use the taxonomy method for a simplified formalization of food security index calculations. The proposed method makes it possible to assess the degree of cumulative influence of factor characteristics on the level of state food security. The research was used publicly available, reliable and representative indicators with statistical significance. The formalized indicators of food security according to the Methodological recommendations are: average daily caloric content of human nutrition; ratio of production and consumption volumes: meat products, milk and dairy products, eggs, oil, sugar, potatoes, vegetables and food melon crops; production of grain per person per year; the level of stocks of grain crops; the share of sales imported food products through the trade network of enterprises. The use of the taxonomy method as methodical research is determined to the search for a generalizing integral indicator among a significant number of indicators (multiple signs that have a vector character), which form the most significant impact on the overall level of food security and contribute to the sustainable development of agriculture. A step-by-step algorithm was used to calculate the food security on the basis of taxonomic analysis: a system of indicators (multiple signs) is defined for evaluating the integral indicator of the level of food security for the retrospective period from 2015 to 2021, which create a weighted (stimulating, disincentive) contribution to the overall food security index. In accordance with the rules of the taxonomic procedure, the indicators of the input matrix were normalized, the coordinates of the reference point were determined, the deviation between individual indicators and the base comparison was determined, and the integral (taxonomic) indicator of the level of food security of Ukraine was calculated.
Keywords: продовольча безпека; food security; економіко-математичні методи; economic and mathematical methods; таксономічний аналіз; taxonomic analysis; taxonomic indicator; таксономічний показник; показники-індикатори; indicators; кафедра економіки і права; кафедра маркетингу